2021
DOI: 10.3390/jcm10050981
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Complications of Intravitreal Anti-VEGF Injections

Abstract: Intravitreal injection of anti-vascular endothelial growth factor (anti-VEGF) agents is a commonly used therapy for numerous retinal diseases. The most commonly used of these medications are bevacizumab, ranibizumab, aflibercept, and brolucizumab. However, intravitreal administration of these agents is also associated with several inflammatory and non-inflammatory adverse events. The three inflammatory adverse events are sterile intraocular inflammation, brolucizumab-associated retinal vasculitis, and post-inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 88 publications
2
87
0
3
Order By: Relevance
“…As for safety, we found that high titers of rAAV2.7m8 and rAAV2 expressing KH902 resulted in a vascular sheathing pathology that is associated with immune cell infiltration. A similar pathology has also been reported in patients receiving anti-VEGF treatment who experienced a worsening in vision 3,19,20 (NCT04418427). We show that this phenotype is associated with increased expression of intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1), two proteins that are essential for extravasation of immune cells by increasing vessel wall interaction with immune cells.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…As for safety, we found that high titers of rAAV2.7m8 and rAAV2 expressing KH902 resulted in a vascular sheathing pathology that is associated with immune cell infiltration. A similar pathology has also been reported in patients receiving anti-VEGF treatment who experienced a worsening in vision 3,19,20 (NCT04418427). We show that this phenotype is associated with increased expression of intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1), two proteins that are essential for extravasation of immune cells by increasing vessel wall interaction with immune cells.…”
Section: Introductionsupporting
confidence: 72%
“…Inflammatory complications after intravitreal delivery of anti-VEGF drugs have been documented for all drugs currently in use 3 . Recent clinical findings reported the occurrence of ocular vasculitis with associated decrease in vision in some wet AMD patients who received an intravitreal injections of a novel anti-VEGF antibody that is smaller and presumably may diffuse better to the back of the eye 19,20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there was an increased risk of developing retinal scarring and geographic atrophy in nAMD patients 2 to 5 years after initiating treatment [ 14 ]. Complications such as vitreous and subconjunctival hemorrhage, fluid accumulation under the fovea, increased intraocular pressure, endophthalmitis, and ocular inflammation have also been described [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%